International Law and the Rule of Law under Extreme Conditions An Economic Perspective. Contributions to the XIVth Travemünde Symposium on the Economic Analysis of Law (March 27-29, 2014) - Oeter, Stefan; Voigt, Stefan; Eger, Thomas (Mohr Siebeck, 2017)
The contributions to this volume are a result of the XIVth Travemünde Symposium on the economic analysis of law. Economists and jurists from Europe and non-European countries discuss how natural disasters, civil wars or economic collapses affect international law.
PublicationDate: 20170606
Keywords: Völkerrecht -- Internationalisierung -- Globalisierung -- Institutionenökonomik